História na educação matemática - um estudo sobre trabalhos publicados no Brasil nos últimos cinco anos - Souto, Romélia Mara Alves [UNESP] (My University, 2010)
In this paper we report a study on research in the field of History in Mathematics Education conducted in Brazil in the last five years. We evaluate studies that are theoretical or report experiences on the support found in history that can contribute to the situations of teaching and learning of mathematics, based on the Proceedings of Seminários Nacionais de História da Matemática and Encontros Luso-Brasileiros de História da Matemática. Examining the interests, directions and focus of research in the field, we found that the vast majority of studies address specific issues of History of Mathematics, and the number of studies on History in Mathematics Education is still very low. We note that, in the last five years, the arguments in favor of the teaching potential of the History of Mathematics, which is very present in the speech of teachers and managers of public education, has not yet been materialized in experiments or investigations to promote this link effectively.
History in mathematics education - A study of research published in Brazil in the last five years
Keywords: History in Mathematics Education; History of Mathematics; Mathematics Education